Corn (Zea mays L.) and sorghum (Sorghum bicolor (L.) Moench) yield and nutritional quality affected by drought stress. (October 2022) - Safian, Nasrin; Naderi, Mohammad Reza; Torabi, Masoud; Soleymani, Ali; Salemi, Hamid Reza
Abstract: Comparison of drought tolerance of crop plants is important for planning efficient cropping strategies and increasing yield production. The objective was to investigate the effects of drought stress including control (S1), 80 (moderate, S2) and 60% (severe, S3) of crop essential irrigation (determined by evaporation from the Class A evaporation pan) on grain yield and nutritional quality of different corn ( Zea mays L.) (Maxima (sensitive) and 704 (tolerant)) and sorghum ( Sorghum bicolor (L.) Moench) (Kimia (sensitive) and Payam (tolerant)) genotypes. The experiment, conducted in 2019, was a split plot based on randomized complete block design with three replicates. Plants yields and nutritional quality including relative water content (RW), fiber, protein, starch, tannin, and chlorophyll were measured. Although water stress did not significantly affect RW in corn, it significantly affected RW in sorghum. Fiber concentration was the highest at the severe stress in both corn genotypes (9.36% in 704 and 10.35% in Maxima), and sorghum Payam genotype (14.54%). The lowest (13.29%) and the highest (14.35%) corn protein content were obtained for Maxima in the medium and control level of stress, and for 704 genotype it ranged from 13.51 to 13.77%. Sorghum protein was the highest in the sensitive and tolerant genotypes in control and severe stress, respectively. Treatments S3 and S2 resulted in the highest (14.58%) and the lowest (12.47%) protein content for sorghum Kimia genotype. Although sorghum plants were tolerant in stress conditions, corn plants could also tolerate the stress up to some level by adjusting their physiological characteristics. Highlights: Drought stress significantly affected corn and sorghum yield and nutritional quality. Fiber concentration was the highest at the severe stress in both corn genotypes. Sorghum Payam genotype (14.54%) had the highest fiber in severe stress. Sorghum tolerant genotype had the highest protein in severe stress. The two plants adapted themselves to the stress by improving their physiology.